Trimetallic palladium–copper–cobalt alloy wavy nanowires improve ethanol electrooxidation in alkaline medium. Issue 41 (6th September 2019) - Zhao, Fengling; Li, Chaozhong; Yuan, Qiang; Yang, Fang; Luo, Bin; Xie, Zixuan; Yang, Xiaotong; Zhou, Zhiyou; Wang, Xun
Abstract : This study presents an example of how to prepare low-palladium PdCuCo alloy nanowires as improved anode electrocatalysts for direct ethanol fuel cells. Abstract : Recently, engineering high performance Pd-based nanocatalysts for alkaline ethanol fuel cells has attracted wide attention. Here, we report a one-pot synthesis of low-palladium ternary palladium–copper–cobalt (PdCuCo) alloy nanowires (NWs) with a diameter of ∼4.0 nm to improve the mass activity (MA) of ethanol electrooxidation in alkaline medium. The MA (7.45 A mg −1 ) of the Pd31 Cu61 Co8 NWs is 8.5-fold and 12.4-fold that of commercial Pd black and Pd/C, respectively. The reaction mechanism of the EOR and the reasons for the activity enhancement on Pd31 Cu61 Co8 NWs are elucidated based on the results of in situ Fourier transform infrared spectroscopy and structure characterization. Besides the electronic effect and surface defect sites, the coexistence of surface Cu and Co that have high capacities to activate water to produce reactive oxygen species is another key factor. This study shows an example of how to design low-palladium ternary PdCuCo NWs as improved anode electrocatalysts for alkaline direct ethanol fuel cells with high mass activity.